Pharmacokinetics of Basiliximab for the Prevention of Graft‐versus‐Host Disease in Patients Undergoing Hematopoietic Cell Transplantation with Minimal‐Intensity Cyclophosphamide and Fludarabine. Issue 1 (20th December 2019) - Podichetty, Jagdeep T.; Brinda, Bryan J.; Nelson, Robert P.; Karr, Alissa H.; Prasad, Nagendra K.; Quinney, Sara; Foxworthy Scott, Susanna; Kiel, Patrick J.
Abstract : Study Objective: Basiliximab is an immunosuppressive monoclonal antibody used for rejection prevention following solid organ transplantation; the pharmacokinetics (PK) of basiliximab in this setting are known. Basiliximab may also be used for prophylaxis and treatment of graft‐versus‐host disease (GVHD) in patients undergoing allogeneic hematopoietic cell transplantation (HCT); however, the PK of basiliximab in this setting are not known. Clinical transplant providers expect variation in the volume of distribution and clearance after nonmyeloablative allogeneic transplantation (NMAT) compared with solid organ transplantation. Blood loss, organ site–specific antibody accumulation, and differences in blood product use during the two transplantation approaches may generate differences in basiliximab PK. Therefore, the objective of this study was to describe the PK of basiliximab after its addition to a minimally intense NMAT regimen, in conjunction with cyclosporine, for GVHD prophylaxis in patients with hematologic malignancies. Design: Population PK analysis of a single‐center, single‐arm, phase II clinical trial. Setting: Academic cancer research center. Patients: Fourteen adults with hematologic malignancies (acute myeloid leukemia, acute lymphoblastic leukemia, chronic lymphocytic leukemia, myelodysplastic syndrome, non‐Hodgkin's lymphoma, Hodgkin's lymphoma, myelofibrosis, or severe aplastic anemia) and undergoing NMAT with a fully HLA‐matched (10 of 10 antigen matched) related or unrelated donor. Measurements and Main Results: Basiliximab was used in conjunction with cyclosporine to deplete activated T cells in vivo as GVHD prophylaxis. We developed a novel competitive enzyme‐linked immunosorbent assay (ELISA) method using recombinant interleukin‐2 receptor alpha‐chain (IL‐2Ra) and a commercially available soluble sIL‐2R ELISA kit to permit the quantification of serum basiliximab concentrations and characterization of the PK properties of the drug in this patient population. Using a nonlinear mixed effects model with NONMEM software, a one‐compartment model with first‐order elimination best described the PK, as covariate analysis using stepwise covariate modeling did not improve the base model. Conclusion: We suggest a one‐compartment population model with first‐order elimination to capture the PK profile for basiliximab for this patient population.